Auditors' introduction to crytography and its application in database security - Zailani Mohamed Sidek, Assoc.Prof.Dr.; Norbik Bashah Idris; Harihodin Selamat; International Arab Conference on Information Technology (2002 : University of Qatar, Doha, Qatar) (Skudai : Universiti Teknologi Malaysia, 2002)
57